Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Basically, I'm trying to prove (by induction) that:

$$1+\frac{1}{\sqrt{2}}+\frac{1}{\sqrt{3}}+\dots+\frac{1}{\sqrt{n}} > 2\:(\sqrt{n+1} − 1)$$

I know to begin, we should use a base case. In this case, I'll use $1$. So we have:

$$1 > 2\:(1+1-1) = 1>-2$$

Which works out.

My problem is the next step. What comes after this? Thanks!

share|improve this question
3  
For $n=1$, the inequation should be $1>2(\sqrt2-1)$ which is indeed true, but not that trivial. Anyway, neither $2(1+1-1)=1$ is valid, and don't know where that $-2$ is coming from... –  Berci Feb 25 '13 at 12:03
    
The defacing of this user's questions continues... This time, the modifications are absurd. –  Did May 6 '13 at 19:35
    
Rolled back. Read the rules wrong, my bad! –  stevenmadden May 6 '13 at 20:16

4 Answers 4

up vote 17 down vote accepted

Mean Value Theorem can also be used,

Let $\displaystyle f(x)=\sqrt{x}$

$\displaystyle f'(x)=\frac{1}{2}\frac{1}{\sqrt{x}}$

Using mean value theorem we have:

$\displaystyle \frac{f(n+1)-f(n)}{(n+1)-n}=f'(c)$ for some $c\in(n,n+1)$

$\displaystyle \Rightarrow \frac{\sqrt{n+1}-\sqrt{n}}{1}=\frac{1}{2}\frac{1}{\sqrt{c}}$....(1)

$\displaystyle \frac{1}{\sqrt{n+1}}<\frac{1}{\sqrt{c}}<\frac{1}{\sqrt{n}}$

Using the above ineq. in $(1)$ we have,

$\displaystyle \frac{1}{2\sqrt{n+1}}<\sqrt{n+1}-\sqrt{n}<\frac{1}{2\sqrt{n}}$

Adding the left part of the inequality we have,$\displaystyle\sum_{k=2}^{n}\frac{1}{2\sqrt{k}}<\sum_{k=2}^{n}(\sqrt{k}-\sqrt{k-1})=\sqrt{n}-1$

$\Rightarrow \displaystyle\sum_{k=2}^{n}\frac{1}{\sqrt{k}}<2\sum_{k=2}^{n}(\sqrt{k}-\sqrt{k-1})=2(\sqrt{n}-1)$

$\Rightarrow \displaystyle1+\sum_{k=2}^{n}\frac{1}{\sqrt{k}}<1+2\sum_{k=2}^{n}(\sqrt{k}-\sqrt{k-1})=2\sqrt{n}-2+1=2\sqrt{n}-1$

$\Rightarrow \displaystyle\sum_{k=1}^{n}\frac{1}{\sqrt{k}}<2\sqrt{n}-1$

Similarly adding the right side of the inequality we have,

$\displaystyle\sum_{k=1}^{n}\frac{1}{2\sqrt{k}}>\sum_{k=1}^{n}(\sqrt{k+1}-\sqrt{k})=\sqrt{n+1}-1$

$\Rightarrow \displaystyle\sum_{k=1}^{n}\frac{1}{\sqrt{k}}>2(\sqrt{n+1}-1)$

This completes the proof.

$\displaystyle 2\sqrt{n+1}-2<\sum_{k=1}^{n}{\frac{1}{\sqrt{k}}}<2\sqrt{n}-1.$

This is a much better proof than proving by induction(Ofcourse if someone knows elementary calculus).

share|improve this answer
1  
Nice! The mean value theorem (or just the idea of using functions) would never have crossed my mind. –  genepeer Feb 25 '13 at 12:03

Let $f(x) = \frac{1}{\sqrt{x}}$. This is a decreasing function on $\mathbb{R}^+_*$, hence $$ f(k) > \int_k^{k+1} f(x) \, \mathrm{d}x. $$ Summing for $k=1, \dots, n$ give $$ f(1) + f(2) + \dots + f(n) > \int_1^{n+1} f(x) \, \mathrm{d}x,$$ which is exactly the desired inequality.

share|improve this answer

Hint(for induction):

$$2(\sqrt{n+1}-1)+\dfrac{1}{\sqrt{n+1}}>2(\sqrt{n+2}-1)\iff \\ 2n+3>2\sqrt{(n+2)(n+1)}\iff \\ (2n+3)^2>4(n+2)(n+1)=(2n+3)^2-1\cdots$$

share|improve this answer

We can prove that for $x \geqslant 1$ \begin{align*}\sum_{1\leqslant n\leqslant x}\frac{1}{\sqrt{n}}&\overset{*}=\frac{[x]}{\sqrt{x}}+\frac{1}{2}\int\limits_1^x\frac{[t]}{t^{3/2}}\,dt\\ &=\frac{x+\mathcal{O}(1)}{\sqrt{x}}+\frac{1}{2}\int\limits_1^x\frac{t-\{t\}}{t^{3/2}}\,dt\\ &=\sqrt{x}+\mathcal{O}\left(\frac{1}{\sqrt{x}}\right)+\frac{1}{2}\int\limits_1^x\frac{dt}{\sqrt{t}}-\frac{1}{2}\int\limits_1^{\infty}\frac{\{t\}}{t^{3/2}}\,dt+\frac{1}{2}\int\limits_x^{\infty}\frac{\{t\}}{t^{3/2}}\,dt\\ &=2\sqrt{x}-1-\frac{1}{2}\int\limits_1^{\infty}\frac{\{t\}}{t^{3/2}}\,dt+\mathcal{O}\left(\frac{1}{\sqrt{x}}\right)\\ &=2\sqrt{x}+c+\mathcal{O}\left(\frac{1}{\sqrt{x}}\right),\end{align*} where $\displaystyle c\overset{\text{def}}{=}-1-\frac{1}{2}\int\limits_1^{\infty}\frac{\{t\}}{t^{3/2}}\,dt $ is some absolute real constant.

$*$ - we used here Abel's summation formula for $ a_n=1 $ and $ \phi(n)=\dfrac{1}{\sqrt{n}} $

$[\,\,]$ denotes floor function and $ \{\,\,\} $ fractional part function

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.